Choices Based on the Self-Perception of University Applicants in their Decisions on Applying to Higher Education - Attila Miklós; Eszter Lukács (Decision Making: Applications in Management and Engineering, 2024)
This paper investigates the role of self-concept and perceptions of academic performance in shaping university students’ choice of educational institutions, as well as the factors that influence these decisions. Various empirical studies have examined this topic, identified key determinants and reflected the aspects and expectations that students prioritize when making decisions about their academic future. In this study, we utilized scientific databases to filter through thousands of papers, ultimately selecting 225 articles that were directly related to decision-making processes in education. Out of these, we have cited 60 publications that offer significant insights relevant to our research. Moreover, we identified 20 empirical studies that specifically analyse the factors that influence students’ decision-making processes, based on data gathered through questionnaires and interviews. To further explore students’ career aspirations and understand the factors influencing their choices, we focus on several key variables. These include students’ self-perception, self-confidence, and personal development. We also assess how external factors, such as socioeconomic conditions, family expectations, and educational environment, may impact these decisions. By examining these elements, we aim to uncover how such influences contribute to students’ educational and professional trajectories. This study seeks to clarify how diverse influences, particularly those experienced during adolescence, shape individuals’ personal growth and career pathways. In addition, it aims to identify any gaps in existing research, especially with regard to international practices and trends, thereby contributing to the broader understanding of student decision-making in higher education